Unstable Education System Inducing Mental Stress in COVID-19 Lockdown - Singh, Gurjant (Open Access Macedonian Journal of Medical Sciences, 2020)
Coronavirus disease or COVID-19 caused by SARS-CoV-2 has triggered a respiratory tract infection claiming more than 3 lakh lives worldwide with 4.5 million cases and still counting. This is the worst hit of the 21st century which has made it to be announced as a pandemic by WHO on March 11, 2020. It is not possible at the time to comment if the virus has appeared all of a sudden or its gradual emerging in a short or long time with information passed lately. However, the virus has adjourned the life of humans in almost every aspect with most of the countries, including India announcing nationwide lockdowns. The news of progress over medicine or vaccine over days is no doubt giving hope to the stressed-out humanity which is being striked out again by some higher health officials warning that the coronavirus may never go away. Such news is always creating panic and claiming mental peace, building more stress in individuals. Amidst all these crisis, there is a field which took everyone’s attention, that is the education of the students. However, Indians are always known to emerge out stronger in challenges, so did they, when it was the matter of future of the students. Although Indian education system is not much familiar to such measures, it was the call and need of the situation to clasp to a different mode of education effectively and efficiently. Even with this much dedication, there seem to be some points on which the education system is breaking down gradually without the awareness of many. This article has focused on a few of such challenges imposed by the COVID-19 lockdown on the education system in India.